2013
DOI: 10.3390/molecules18010768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selected Polysorbate and Sucrose Ester Emulsifiers on the Physicochemical Properties of Astaxanthin Nanodispersions

Abstract: The effects of selected nonionic emulsifiers on the physicochemical characteristics of astaxanthin nanodispersions produced by an emulsification/evaporation technique were studied. The emulsifiers used were polysorbates (Polysorbate 20, Polysorbate 40, Polysorbate 60 and Polysorbate 80) and sucrose esters of fatty acids (sucrose laurate, palmitate, stearate and oleate). The mean particle diameters of the nanodispersions ranged from 70 nm to 150 nm, depending on the emulsifier used. In the prepared nanodispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 21 publications
4
43
1
Order By: Relevance
“…This finding might be explained by the increasing interference caused by the growing number of polysorbate molecules, which prevented the efficient diffusion of the organic phase into the aqueous phase. To the best of our knowledge, there are three other studies by Anarjan and Tan (2013), Cheong, Mirhosseini, and Tan (2010) and Saberi et al (2013), which were similar to our study in the sense that all three studies involved the fabrication of different nanoemulsions/nanodispersions by using Tween 20, 40, 60 and 80 (in the case of Cheong et al (2010), they used only Tween 20, 60 and 80). In their respective studies, Anarjan and Tan (2013) and Cheong et al (2010) found that, among all the Tween emulsifiers used, Tween 20…”
Section: Effects Of Different Polysorbate (Tween) Emulsifierssupporting
confidence: 80%
See 3 more Smart Citations
“…This finding might be explained by the increasing interference caused by the growing number of polysorbate molecules, which prevented the efficient diffusion of the organic phase into the aqueous phase. To the best of our knowledge, there are three other studies by Anarjan and Tan (2013), Cheong, Mirhosseini, and Tan (2010) and Saberi et al (2013), which were similar to our study in the sense that all three studies involved the fabrication of different nanoemulsions/nanodispersions by using Tween 20, 40, 60 and 80 (in the case of Cheong et al (2010), they used only Tween 20, 60 and 80). In their respective studies, Anarjan and Tan (2013) and Cheong et al (2010) found that, among all the Tween emulsifiers used, Tween 20…”
Section: Effects Of Different Polysorbate (Tween) Emulsifierssupporting
confidence: 80%
“…By contrast, Saberi et al (2013) noted that among these four types of Tween emulsifiers, Tween 80 produced nanoemulsions with the smallest particle sizes, whereas the largest particle size was obtained when Tween 60 was used, although both Tween 60 and Tween 80 have similar HLB values (the HLB for Tween 60 is 14.9 and the HLB for Tween 80 is 15.0). In comparing our findings with all three studies, we found that our observations were similar to those of Saberi et al (2013), but they were the exact opposite of the observations noted by Anarjan and Tan (2013) and Cheong et al (2010). In our case, Tween 80 produced smaller particle sizes when compared with Tween 20.…”
Section: Effects Of Different Polysorbate (Tween) Emulsifierscontrasting
confidence: 69%
See 2 more Smart Citations
“…Due to the long conjugated unsaturated double bond in the molecular structure of astaxanthin its properties are extremely unstable. Oxygen, light, heat and metal ions can cause damage to astaxanthin, causing it to oxidize or degrade . Astaxanthin possesses two identical asymmetric carbon atoms at C‐3 and C‐3 making three possible isomers with all‐transconfiguration of the chain: 1.)…”
Section: Marine Plant Sourcesmentioning
confidence: 99%